The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s40262-022-01173-8
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine Release Syndrome and/or the Proinflammatory Cytokines as Underlying Mechanisms of Downregulation of Drug Metabolism and Drug Transport: A Systematic Review of the Clinical Pharmacokinetics of Victim Drugs of this Drug–Disease Interaction Under Different Clinical Conditions

Abstract: Background and Objective An ever-growing body of evidence supports the impact of cytokine modulation on the patient’s phenotypic drug response. The aim of this systematic review was to analyze the clinical studies that assessed the pharmacokinetics of victim drugs of this drug–disease interaction in the presence of different scenarios of cytokine modulation in comparison with baseline conditions. Methods We conducted a systematic review by searching the PubMed-MEDLINE d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…35 Indeed, a growing number of in vitro and clinical studies have shown that several immune mediators, especially IL-6, moderately downregulate the activity of CYP3A4 and weakly-to-moderately downregulate those of CYP2C19. 36,37 In critically ill patients with CAPA, Gatti et al found that Creactive protein and procalcitonin values, inflammatory biomarkers, above defined thresholds could cause voriconazole overexposure, leading to potentially toxic concentrations. 38 In patients with invasive fungal disease, Vreugdenhil et al reported voriconazole C min had a moderate correlation with systemic IL-6 responses, consistent with our prediction (Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…35 Indeed, a growing number of in vitro and clinical studies have shown that several immune mediators, especially IL-6, moderately downregulate the activity of CYP3A4 and weakly-to-moderately downregulate those of CYP2C19. 36,37 In critically ill patients with CAPA, Gatti et al found that Creactive protein and procalcitonin values, inflammatory biomarkers, above defined thresholds could cause voriconazole overexposure, leading to potentially toxic concentrations. 38 In patients with invasive fungal disease, Vreugdenhil et al reported voriconazole C min had a moderate correlation with systemic IL-6 responses, consistent with our prediction (Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, implementing a TDM-based expert clinical pharmacological advice program for optimizing voriconazole exposure should become mandatory even in CAPA critically ill patients [ 20 , 31 ], as previously recommended for other settings [ 10 , 32 ]. In this scenario, the careful assessment of the degree of inflammation should be taken into account in the personalization of voriconazole therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole metabolism is mediated by CYP2C9, CYP2C19, and CYP3A4 [ 18 ]. Indeed, an ever-growing number of studies showed that several pro-inflammatory cytokines, especially IL-6, may moderately downregulate the activity of CYP3A4 and weakly-to-moderately downregulate those of CYP2C9 and CYP2C19 [ 19 , 20 ]. Considering that inflammation represents a common feature that shows remarkable proportion among ICU patients, a relevant impact on the occurrence of voriconazole overexposure and toxicity could not be ruled out [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It could be due to the concomitant effect of the CYP2C19 gene polymorphism and inflammatory response on hepatic cytochrome CYP2C19 enzyme activity. A meta-analysis by Milo Gatti and Federico Pea of 26 studies found that an inflammatory response decreased CYP2C19 enzyme activity (as demonstrated by a 1.29–1.97-fold dropping in omeprazole clearance) [ 15 ]. Another study was conducted to investigate the effect of inflammation (via a tablet marker, CRP index) on cytochrome P450 activity in the liver.…”
Section: Discussionmentioning
confidence: 99%